Preparation method of sulfur-poly (ionic liquid) copolymer composite positive electrode and lithium-sulfur battery
By using sulfur @ polyion liquid copolymer composite in the positive electrode of lithium sulfur battery, the problems of limited electron conduction capacity and insulation are solved, and the conductivity and cycling performance of the battery are significantly improved.
Patent Information
- Application Number
- CN202411780500.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-05
AI Technical Summary
The existing conductive polymer composite sulfur positive electrode materials have limited electron conductivity, poor permeability of electrolytes, and insulating properties of sulfur and lithium sulfide in lithium sulfur batteries, which limits their practical application in the positive electrode modification of lithium sulfur batteries.
The preparation method of sulfur @ polyion liquid copolymer composite positive electrode is adopted. By mixing the ionic liquid with sulfur powder and ball milling, a semi-coated polyion liquid copolymer is formed, thereby enhancing the ion transfer rate and electrochemical stability of the positive electrode.
It significantly improves the conductivity and chemical stability of lithium-sulfur batteries, and improves its cycling and rate performance under different current densities.
Smart Images

Figure CN119601595A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of batteries, and in particular relates to a method for preparing a sulfur@polyionic liquid copolymer composite positive electrode and a lithium-sulfur battery. Background Art
[0002] Due to its special physical and chemical properties, the combination of polymers with active sulfur is still the key to achieve positive electrode modification. Polymers usually have rich functional groups, which have strong chemical adsorption effects on polysulfides and can effectively inhibit the shuttling effect of polysulfides. Conductive polymers are the most widely used polymers. Based on these advantages, more and more studies have been conducted on their use in lithium-sulfur batteries in recent years. There are two main forms of composites of conductive polymers and S: one is to form a core-shell structure of "polymer-encapsulated S", such as polythiophene (PTh) / S, polypyrrole (PPy) / S, polyvinylcarbazole (PVK) / S, polyaniline (PANi) / S and poly(3, 4-ethylenedioxythiophene) (PEDOT) / S composites, which mainly rely on the physical confinement of S in the polymer shell to stabilize the positive electrode and show good electrochemical performance. The other is the core-shell structure of "S-encapsulated polymer", such as compounding S to the surface of a conductive polymer matrix (mainly including PPy nanowires and nanotubes, PANi nanotubes and hollow PANi spheres, etc.) by melting or chemical deposition. The polymer plays the role of a conductor, dispersant, adsorbent and buffer for volume changes in the composite material, and provides a better carrier for the deposition of S.
[0003] Although conductive polymer composite sulfur cathode materials have shown significant advantages in the modification of lithium-sulfur battery cathodes, they still face the following challenges in practical applications: (1) The commonly used conductive polymers generally have a non-localized π-electron conjugated structure, which makes their ability to conduct electrons limited, and they still need to be further enhanced through copolymerization or doping. (2) Conductive polymer materials are generally very rigid, which is not conducive to the penetration of electrolytes and the formation of ion conductive networks, and the inhibitory effect on electrode volume expansion is not ideal. (3) The adsorption and fixation effect on polysulfides is still relatively weak, and more importantly, it cannot solve the problem of sulfur and lithium sulfide ion insulation. This defect will also greatly limit the practical application of composite materials in the modification of lithium-sulfur battery cathodes.
[0004] Polyionic liquid (PIL) is a special type of polymer formed by the polymerization of ionic liquid monomers. It has excellent physical and chemical stability, such as high temperature stability and anti-oxidation, which makes it perform well in demanding environments. In addition, polyionic liquid also has good ionic conductivity, which makes it widely used in the field of electrochemistry and is often used as electrolytes for energy devices such as batteries, fuel cells and capacitors. The present invention uses the above advantages and attempts to apply polymeric ionic liquid (PIL) to the modification of positive electrode materials for the first time, and develops a method for preparing a sulfur@polyionic liquid copolymer composite positive electrode and a lithium-sulfur battery to solve some of the defects in the above technical background. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a method for preparing a sulfur@polyionic liquid copolymer composite positive electrode and a lithium-sulfur battery. In the polyionic liquid copolymer prepared in the present application, part of the sulfur powder surface is coated with the polymerized ionic liquid, which can enhance the ion transfer rate and electrochemical stability of the positive electrode; the remaining sulfur powder surface is not coated with the polymerized ionic liquid, and the remaining sulfur powder is exposed, which can be combined with a conductive agent to enhance the conductivity of the positive electrode. The sulfur@polyionic liquid copolymer composite positive electrode of the present application can make the lithium-sulfur battery have excellent conductivity and chemical stability, and can greatly improve the cycle performance and rate performance of the lithium-sulfur battery at different current densities.
[0006] To this end, the present invention provides a method for preparing a sulfur@polyionic liquid copolymer composite positive electrode, comprising: (1) mixing the ionic liquid and the solvent, adding the lithium salt and the initiator, and stirring until the solution is clear and transparent to obtain a precursor solution; (2) mixing the precursor solution and sulfur powder into a beating box for ball milling, and then drying to obtain a sulfur@polyionic liquid copolymer; (3) A positive electrode slurry is prepared using sulfur@polyionic liquid copolymer, conductive graphite, acetylene black and polyvinylidene fluoride (PVDF) as raw materials; the positive electrode slurry is coated on a carbon-coated aluminum foil and dried to obtain a sulfur@polyionic liquid copolymer composite positive electrode.
[0007] Preferably, in step (1), the ionic liquid is at least one of 1-vinyl-3-butylimidazole trifluoromethanesulfonyl imide, 1-propenyl-3-methylimidazole and 1,4-bis(3-vinylimidazole)dibromobutane.
[0008] Preferably, in step (1), the solvent is N-methylpyrrolidone NMP, and the ratio of the mass of the ionic liquid to the volume of the solvent is (0.5-1.5) g: (1500-3000 uL).
[0009] Preferably, in step (1), the lithium salt comprises lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and / or lithium hexafluorophosphate (LiPF6), and the mass of the lithium salt is 30%-50% of the mass of the ionic liquid.
[0010] Preferably, in step (1), the initiator comprises azobisisobutyronitrile (AIBN) and / or azobisisoheptanenitrile, and the mass of the initiator is 0.5%-3% of the mass of the ionic liquid.
[0011] Preferably, in step (2), the mass ratio of the ionic liquid to the sulfur powder is (30-40): (70-150).
[0012] Preferably, in step (2), the ball milling speed is 200-400 r / min, and the ball milling time is 40-55 h; the drying process includes: drying in a blast oven for 10-15 h, and then drying in a vacuum oven for 10-15 h.
[0013] Preferably, in step (3), the mass ratio of sulfur@polyionic liquid copolymer: conductive graphite: acetylene black: PVDF is (60-70): (10-20): (10-20): (3-9).
[0014] Preferably, in step (3), the thickness of the sulfur@polyionic liquid copolymer composite positive electrode is 200-300 um and the diameter is 7-15 mm.
[0015] The present invention also provides a lithium-sulfur battery, comprising a lithium negative electrode, a polyethylene separator, and a positive electrode, wherein the positive electrode is a sulfur@polyionic liquid copolymer composite positive electrode prepared by the preparation method of the sulfur@polyionic liquid copolymer composite positive electrode.
[0016] Compared with the prior art, the advantages and positive effects of the present invention are: (1) The preparation process of the sulfur@polyionic liquid copolymer of the present application is carried out at room temperature, has low environmental requirements, and does not require the preparation of a template in advance, and has the advantages of being simple, easy to operate, and energy-saving. The production efficiency of the sulfur@polyionic liquid copolymer is high and can be mass-produced.
[0017] (2) The ionic liquid of the present application can effectively and uniformly polymerize in situ on the surface of the sulfur powder, achieve controllable coating, and ensure the formation of a polyionic liquid copolymer with a semi-coated morphology and a core-shell structure. In the polyionic liquid copolymer prepared in the present application, part of the sulfur powder surface is coated with the polymerized ionic liquid, which can enhance the ion transfer rate and electrochemical stability of the positive electrode; the remaining part of the sulfur powder surface is not coated with the polymerized ionic liquid, and the remaining part of the sulfur powder is exposed, which can be combined with the conductive agent to enhance the conductivity of the positive electrode. The sulfur@polyionic liquid copolymer composite positive electrode of the present application can make the lithium-sulfur battery have excellent conductivity, chemical stability, and can greatly improve the cycle performance and rate performance of the lithium-sulfur battery at different current densities.
[0018] (3) The ionic liquid of the present application is preferably 1-vinyl-3-butyl imidazole trifluoromethanesulfonyl imide salt, which has excellent ion conductivity, high thermal stability, excellent chemical stability, and low volatility. It can effectively block the dissolution of sulfur and polysulfides while increasing the ion conductivity of sulfur. Secondly, the polymeric ionic liquid has excellent flexibility and mechanical stability, which is conducive to the penetration of electrolyte and the formation of ion conductive network. It has a good buffering effect on the volume expansion and / or volume contraction of sulfur during battery charging and discharging, ensures the structural stability of the positive electrode, and can greatly improve the cycle performance and rate performance of lithium-sulfur batteries at different current densities. In addition, the polymeric ionic liquid contains abundant CF bonds, has excellent fixation and absorption effect on polysulfides, and can effectively block the dissolution of polysulfides.
[0019] After reading the specific embodiments of the present invention in conjunction with the accompanying drawings, other features and advantages of the present invention will become more clear. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a SEM morphology image of the sulfur@polyionic liquid copolymer composite positive electrode prepared in Example 1 of the present invention; Figure 2 This is the SEM morphology of sulfur powder; Figure 3 The figure is a rate performance test diagram of the lithium-sulfur battery of Example 2 of the present invention and Comparative Example 1; Figure 4 The graphs are the cycle performance test graphs of the lithium-sulfur batteries of Example 2 and Comparative Example 1 of the present invention; Figure 5 This is a visual absorption test diagram of polymerized ionic liquid on polysulfide solution. DETAILED DESCRIPTION
[0021] The present invention will be further described below in conjunction with specific embodiments. These embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. Meanwhile, after reading the present invention, those skilled in the art may make various modifications or changes to the present invention, and these equivalent forms also fall within the scope limited by the appended claims of the application.
[0022] The preparation method of the sulfur@polyionic liquid copolymer composite positive electrode of the present invention comprises: (1) mixing the ionic liquid and the solvent, adding the lithium salt and the initiator, and stirring until the solution is clear and transparent to obtain a precursor solution; The ionic liquid is at least one of 1-vinyl-3-butyl imidazole trifluoromethanesulfonyl imide salt, 1-propylene-3-methyl imidazole, and 1,4-bis(3-vinyl imidazole) dibromobutane.
[0023] The ionic liquid of the present application is preferably 1-vinyl-3-butyl imidazole trifluoromethanesulfonyl imide salt, which has excellent ion conductivity, high thermal stability, excellent chemical stability, and low volatility. It can well block the dissolution of sulfur and polysulfide while increasing the ion conductivity of sulfur; secondly, the polymerized ionic liquid has excellent flexibility and mechanical stability, which is conducive to the penetration of electrolyte and the formation of ion conductive network, and has a good buffering effect on the volume expansion and / or volume contraction of sulfur during battery charging and discharging, ensuring the structural stability of the positive electrode, and can greatly improve the cycle performance and rate performance of lithium-sulfur batteries at different current densities. In addition, the polymerized ionic liquid contains abundant CF bonds, has excellent fixation and absorption effect on polysulfide, and can effectively block the dissolution of polysulfide.
[0024] The solvent is N-methylpyrrolidone NMP, and the ratio of the mass of the ionic liquid to the volume of the solvent is (0.5-1.5) g: (1500-3000 uL); preferably, the ratio of the mass of the ionic liquid to the volume of the solvent is (0.8-1.2) g: (1800-2200 uL).
[0025] The solvent of the present application can make the precursor solution and sulfur powder fully and evenly mixed, and can make the ionic liquid effectively and evenly polymerize in situ on the surface of the sulfur powder to form a polyionic liquid copolymer with a semi-encapsulated morphology and a core-shell structure.
[0026] Lithium salts include lithium bis(trifluoromethanesulfonyl)imide (LiTFSI). LiTFSI has high electrochemical stability and conductivity, and a low probability of side reactions, and can provide electrochemical stability and conductivity for lithium-sulfur batteries.
[0027] The mass of the lithium salt is 30%-50% of the mass of the ionic liquid, preferably, the mass of the lithium salt is 35%-45% of the mass of the ionic liquid; LiTFSI can maximize the ionic conductivity and electrochemical stability of the polyionic liquid copolymer.
[0028] The initiator includes azobisisobutyronitrile AIBN and / or azobisisoheptanenitrile, and the mass of the initiator is 0.5%-3% of the mass of the ionic liquid. Preferably, the mass of the initiator is 0.5%-1.5% of the mass of the ionic liquid.
[0029] The initiator of the present application can initiate the complete polymerization of the ionic liquid, so that the ionic liquid is polymerized evenly on the surface of the sulfur powder, while avoiding the generation of bubbles caused by excessive polymerization of the ionic liquid, and ensuring the formation of a polyionic liquid copolymer with a semi-encapsulated morphology and a core-shell structure.
[0030] By adjusting the amount of lithium salt and initiator used, the present application can make the ionic liquid effectively and evenly polymerize in situ on the surface of the sulfur powder, realize the controllability of the coating, and ensure the formation of a polyionic liquid copolymer with a semi-coated morphology and a core-shell structure. In the polyionic liquid copolymer prepared in the present application, part of the sulfur powder surface is coated with the polymerized ionic liquid, which can enhance the ion transfer rate and electrochemical stability of the positive electrode; the remaining part of the sulfur powder surface is not coated with the polymerized ionic liquid, and the remaining part of the sulfur powder is exposed, which can be combined with the conductive agent to enhance the conductivity of the positive electrode.
[0031] (2) mixing the precursor solution and sulfur powder into a beating box for ball milling, and then drying to obtain a sulfur@polyionic liquid copolymer; The mass ratio of the ionic liquid to the sulfur powder is (30-40): (70-150), preferably, the mass ratio of the ionic liquid to the sulfur powder is (30-35): (80-120); the ionic liquid can be effectively and uniformly polymerized in situ on the surface of the sulfur powder to form a polyionic liquid copolymer with a semi-encapsulated morphology and a core-shell structure.
[0032] The ball milling speed is 200-400 r / min, and the ball milling time is 40-55h. Through ball milling, the ionic liquid can be effectively and uniformly polymerized in situ on the surface of the sulfur powder to form a sulfur@polyionic liquid copolymer with a semi-encapsulated morphology and a core-shell structure.
[0033] The drying process includes: drying in a forced air oven for 10-15 hours, and then drying in a vacuum oven for 10-15 hours.
[0034] (3) A positive electrode slurry is prepared using sulfur@polyionic liquid copolymer, conductive graphite, acetylene black and polyvinylidene fluoride (PVDF) as raw materials; the positive electrode slurry is coated on a carbon-coated aluminum foil and dried to obtain a sulfur@polyionic liquid copolymer composite positive electrode.
[0035] The mass ratio of sulfur@polyionic liquid copolymer: conductive graphite: acetylene black: PVDF is (60-70): (10-20): (10-20): (3-9). When the reaction is carried out within the above mass ratio range, a positive electrode with a stable structure can be obtained, which can improve the ion transfer rate, conductivity and electrochemical stability of the positive electrode.
[0036] The conductive graphite and acetylene black of the present application can effectively solve the problem of sulfur's non-conductivity and effectively enhance the conductivity of the positive electrode.
[0037] The binder PVDF of the present application can ensure the effective adhesion of sulfur@polyionic liquid copolymer, conductive graphite and acetylene black to each other, prevent the sulfur@polyionic liquid copolymer and / or conductive graphite and / or acetylene black from falling off after drying, and ensure the formation of a stable sulfur@polyionic liquid copolymer composite positive electrode.
[0038] The thickness of the sulfur@polyionic liquid copolymer composite positive electrode is 200-300 um and the diameter is 7-15 mm.
[0039] The present invention also provides a lithium-sulfur battery, which is assembled into a button lithium-sulfur battery using a lithium negative electrode, a polyethylene separator, a lithium-sulfur electrolyte and a sulfur@polyether copolymer composite positive electrode prepared by the preparation method of the sulfur@polyether copolymer composite positive electrode described in the present invention.
[0040] The advantages and positive effects of the present invention include: (1) The preparation process of the sulfur@polyionic liquid copolymer of the present application is carried out at room temperature, has low environmental requirements, and does not require the preparation of a template in advance, and has the advantages of being simple, easy to operate, and energy-saving. The production efficiency of the sulfur@polyionic liquid copolymer is high and can be mass-produced.
[0041] (2) The ionic liquid of the present application can effectively and uniformly polymerize in situ on the surface of sulfur powder, realize controllable coating, and ensure the formation of a polyionic liquid copolymer with a semi-coated morphology and a core-shell structure. In the polyionic liquid copolymer prepared in the present application, part of the sulfur powder surface is coated with the ionic liquid, which can enhance the ion transfer rate and electrochemical stability of the positive electrode; the remaining part of the sulfur powder surface is not coated with the ionic liquid, and the remaining part of the sulfur powder is exposed, which can be combined with the conductive agent to enhance the conductivity of the positive electrode.
[0042] (3) The ionic liquid of the present application is preferably 1-vinyl-3-butyl imidazole trifluoromethanesulfonyl imide salt, which has excellent ion conductivity, high thermal stability, excellent chemical stability, and low volatility. It can effectively block the dissolution of sulfur and polysulfides while increasing the ion conductivity of sulfur. Secondly, the polymeric ionic liquid has excellent flexibility and mechanical stability, which is conducive to the penetration of electrolyte and the formation of ion conductive network. It has a good buffering effect on the volume expansion and / or volume contraction of sulfur during battery charging and discharging, ensures the structural stability of the positive electrode, and can greatly improve the cycle performance and rate performance of lithium-sulfur batteries at different current densities. In addition, the polymeric ionic liquid contains abundant CF bonds, has excellent fixation and absorption effect on polysulfides, and can effectively block the dissolution of polysulfides. Example 1
[0043] The preparation method of the sulfur@polyionic liquid copolymer composite positive electrode of this embodiment includes: (1) Take 0.33 g of ionic liquid 1-vinyl-3-butylimidazole trifluoromethanesulfonyl imide salt and mix it with 2000 ul of NMP solution, add 0.132 g of LiTFSI and 0.0033 g of AIBN, and stir until it becomes clear to obtain a precursor solution.
[0044] (2) Mix the precursor solution with 1 g of sulfur powder and put it into a beating box, and ball mill it at a speed of 300 r / min for 48 h. Take it out and dry it in a forced air oven for 12 h, and then transfer it to a vacuum oven for drying for 12 h to obtain the sulfur@polyionic liquid copolymer.
[0045] (3) Using polyvinylidene fluoride (PVDF) as a binder, a positive electrode slurry was prepared in the ratio of sulfur@polyionic liquid copolymer: conductive graphite: acetylene black: PVDF = 65:15:15:5. Then, a 250 um thick positive electrode slurry was scraped onto a carbon-coated aluminum foil, dried, and cut into a disc with a diameter of 10 mm as the positive electrode.
[0046] Figure 1 This is a SEM morphology of the sulfur@polyionic liquid copolymer composite positive electrode prepared in Example 1 of the present invention. Figure 2 is the SEM morphology of sulfur powder; Figure 1 and Figure 2 It can be seen that the surface of blank sulfur is smooth and has no substance coating; while the surface of sulfur@polyionic liquid copolymer is rough and polymer coating is visible to the naked eye, verifying that the polymeric ionic liquid is successfully coated on the sulfur surface.
[0047] Figure 5 This is a visual absorption test chart of the polymeric ionic liquid 1-vinyl-3-butylimidazolium trifluoromethanesulfonyl imide salt polymer of the present application to a polysulfide solution. Figure 5(a) is a photograph of a single polymerized ionic liquid; Figure 5 (b) Initial photograph of adding polysulfide solution to polymerized ionic liquid. Figure 5 (c) is a photo taken after 6 hours of immersion. Figure 5 It can be seen that the polymeric ionic liquid of the present application has an excellent adsorption and fixation effect on polysulfides. Example 2
[0048] The lithium-sulfur battery of this embodiment includes: the sulfur@polyether copolymer of Example 1 as a positive electrode, a lithium sheet as a negative electrode, a 19 mm polyethylene (PE) as a separator, and a button cell assembled using a lithium-sulfur electrolyte.
[0049] Comparative Example 1 The lithium-sulfur battery of this embodiment includes: sulfur S as a positive electrode, a lithium sheet as a negative electrode, 19 mm polyethylene (PE) as a separator, and a button cell assembled using a lithium-sulfur electrolyte.
[0050] Figure 3 The figure is a rate performance test diagram of the lithium-sulfur battery of Example 2 of the present invention and Comparative Example 1, and the figure is a rate performance test diagram of the lithium-sulfur battery after 10 cycles at different current densities (0.1C, 0.2C, 0.5C, 1C, 2C, 0.1C). Figure 3 It can be seen that at each current density, the capacity of the lithium-sulfur battery in Example 2 is higher than that of the lithium-sulfur battery in Comparative Example 1; and when the current density gradually increases and finally returns to the initial 0.1C, the capacity recovery of the lithium-sulfur battery in Example 2 is good.
[0051] Figure 4 This is a cycle performance test diagram of the lithium-sulfur battery of Example 2 of the present invention and Comparative Example 1. This is a cycle performance test diagram of the battery charge and discharge cycle of 200 times at a current density of 0.5C. Figure 4 It can be seen that the lithium-sulfur battery of Example 2 has high capacity, small attenuation, high retention rate, and excellent cycle performance.
[0052] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for a person skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to replace some of the technical features therein by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions claimed to be protected by the present invention.
Claims
1. A method for preparing a sulfur@polyionic liquid copolymer composite positive electrode, characterized in that: include: (1) mixing the ionic liquid and the solvent, adding the lithium salt and the initiator, and stirring until the solution is clear and transparent to obtain a precursor solution; (2) mixing the precursor solution and sulfur powder into a beating box for ball milling, and then drying to obtain a sulfur@polyionic liquid copolymer; (3) A positive electrode slurry is prepared using sulfur@polyionic liquid copolymer, conductive graphite, acetylene black and polyvinylidene fluoride (PVDF) as raw materials; the positive electrode slurry is coated on a carbon-coated aluminum foil and dried to obtain a sulfur@polyionic liquid copolymer composite positive electrode.
2. The method for preparing the sulfur@polyionic liquid copolymer composite positive electrode according to claim 1, characterized in that: In the step (1), the ionic liquid comprises at least one of 1-vinyl-3-butylimidazole trifluoromethanesulfonyl imide salt, 1-propenyl-3-methylimidazole and 1,4-bis(3-vinylimidazole)dibromobutane.
3. The method for preparing the sulfur@polyionic liquid copolymer composite positive electrode according to claim 1, characterized in that: In the step (1), the solvent is N-methylpyrrolidone NMP, and the ratio of the mass of the ionic liquid to the volume of the solvent is (0.5-1.5) g: (1500-3000 uL).
4. The method for preparing the sulfur@polyionic liquid copolymer composite positive electrode according to claim 1, characterized in that: In the step (1), the lithium salt includes lithium bis(trifluoromethanesulfonyl)imide LiTFSI and / or lithium hexafluorophosphate LiPF6, and the mass of the lithium salt is 30%-50% of the mass of the ionic liquid.
5. The method for preparing the sulfur@polyionic liquid copolymer composite positive electrode according to claim 1, characterized in that: In the step (1), the initiator comprises azobisisobutyronitrile (AIBN) and / or azobisisoheptanenitrile, and the mass of the initiator is 0.5% to 3% of the mass of the ionic liquid.
6. The method for preparing the sulfur@polyionic liquid copolymer composite positive electrode according to claim 1, characterized in that: In the step (2), the mass ratio of the ionic liquid to the sulfur powder is (30-40): (70-150).
7. The method for preparing the sulfur@polyionic liquid copolymer composite positive electrode according to claim 1, characterized in that: In the step (2), the ball milling speed is 200-400 r / min and the ball milling time is 40-55h; The drying process includes: drying in a forced air oven for 10-15 hours, and then drying in a vacuum oven for 10-15 hours.
8. The method for preparing the sulfur@polyionic liquid copolymer composite positive electrode according to claim 1, characterized in that: In the step (3), the mass ratio of sulfur@polyionic liquid copolymer: conductive graphite: acetylene black: PVDF is (60-70): (10-20): (10-20): (3-9).
9. The method for preparing the sulfur@polyionic liquid copolymer composite positive electrode according to claim 1, characterized in that: In the step (3), the thickness of the sulfur@polyionic liquid copolymer composite positive electrode is 200-300 um and the diameter is 7-15 mm.
10. A lithium-sulfur battery comprising a lithium negative electrode and a polyethylene separator, characterized in that: It also includes a positive electrode, which is a sulfur@polyionic liquid copolymer composite positive electrode prepared by the preparation method of the sulfur@polyionic liquid copolymer composite positive electrode according to any one of claims 1-9.
Citation Information
Patent Citations
Composite sulfur positive electrode for solid-state lithium-sulfur battery as well as preparation method and application of composite sulfur positive electrode
CN111342001A
Solid electrode and preparation method and application thereof
CN114335525A
Solid-state lithium-sulfur battery with electrode and electrolyte integrated photonic crystal structure and preparation method of solid-state lithium-sulfur battery
CN116525964A
Solid-state battery positive electrode material, production method for solid-state battery positive electrode material, all-solid-state lithium-sulfur battery using solid-state battery positive electrode material, and production method for all-solid-state lithium-sulfur battery using solid-state battery positive electrode material
WO2017155012A1